Genetics of Aggression in Alzheimer’s Disease (AD) - Lukiw, Walter J.; Rogaev, Evgeny I. (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) is a terminal, age-related neurological syndrome exhibiting progressive cognitive and memory decline, however AD patients in addition exhibit ancillary neuropsychiatric symptoms (NPSs) and these include aggression. In this communication we provide recent evidence for the mis-regulation of a small family of genes expressed in the human hippocampus that appear to be significantly involved in expression patterns common to both AD and aggression. DNA array-based gene expression analysis and candidate gene association and/or genome-wide association studies (CGAS, GWAS) of aggressive attributes in humans have revealed a surprisingly small subset of 6 brain genes that are also strongly associated with altered gene expression patterns in AD. These genes encoded on 5 different chromosomes (chr) include the androgen receptor (AR; chrXq12), brain-derived neurotrophic factor (BDNF; chr11p14.1), catechol-O-methyl transferase (COMT; chr22q11.21), neuronal specific nitric oxide synthase (NOS1; chr12q24.22), dopamine beta-hydroxylase (DBH chr9q34.2) and tryptophan hydroxylase (TPH1, chr11p15.1 and TPH2, chr12q21.1). Interestingly, (i) the expression of 3 of these 6 genes (COMT, DBH, NOS1) are highly variable; (ii) 3 of these 6 genes (COMT, DBH, TPH1) are involved in dopamine or serotonin metabolism, biosynthesis and/or neurotransmission; and (iii) 5 of these 6 genes (AR, BDNF, COMT, DBH, NOS1) have been implicated in the development, onset and/or propagation of schizophrenia. The magnitude of the expression of genes implicated in aggressive behavior appears to be more pronounced in the later stages of AD when compared to MCI. These recent genetic data further indicate that the extent of cognitive impairment may have some bearing on the degree of aggression which accompanies the AD phenotype.